"Anterior convergent" chest probing in rapid ultrasound transducer positioning versus formal chest ultrasonography to detect pneumothorax during the primary survey of hospital trauma patients: a diagnostic accuracy study. Issue 1 (December 2015) - Ziapour, Behrad; Haji, Houman
Abstract Background Occult pneumothorax represents a diagnostic pitfall during the primary survey of trauma patients, particularly if these patients require early positive pressure ventilation. This study investigated the accuracy of our proposed rapid model of ultrasound transducer positioning during the primary survey of trauma patients after their arrival at the hospital. Methods This diagnostic trial was conducted over 12 months and was based on the results of 84 ultrasound (US) exams performed on patients with severe multiple trauma. Our index test (US) was used to detect pneumothorax in four pre-defined locations on the anterior of each hemi-thorax using the "Anterior Convergent" approach, and its performance was limited to the primary survey. Consecutively, patients underwent chest-computed tomography (CT) with or without chest radiography. The diagnostic findings of both chest radiography and chest ultrasounds were compared to the gold-standard test (CT). Results The diagnostic sensitivity was 78 % for US and 36.4 % for chest radiography (p < 0.001); the specificity was 92 % for US and 98 % for chest radiography (not significant); the positive predictive values were 74 % for US and 80 % for chest radiography (not significant); the negative predictive values were 94 % for US and 87 % for chest radiography (not significant); the positive likelihood ratio was 10 for US and 18 for chest radiography (p = 0.007); and the negative likelihood ratio was 0.25 for US and 0.65 for chest radiography (p = 0.001). The mean required time for performing the new method was 64 ± 10 s. An absence of the expected diffused dynamic view among ultrasound images obtained from patients with pneumothorax was also observed. We designated this phenomenon "Gestalt Lung Recession." Conclusions "Anterior convergent" chest US probing represents a brief but efficient model that provides clinicians a safe and accurate exam and adequate resuscitation during critical minutes of the primary survey without interrupting other medical staff activities taking place around the trauma patient. The use of the new concept of "Gestalt Lung Recession" instead of the absence of "lung sliding" might improve the specificity of US in detecting pneumothorax.